SUATU TINJAUAN UNSUR EKSTRINSIK PUISI WUNULDE SYAFINAL DAN TAUFIK EFFENDI ARIA DALAM “ARUS” - Sum, Tengku Muhammad (Universitas Lancang Kuning, 2016)
The Analysis of some poems written by Wunulde Syafinal and Taufik Effendi Aria gives general description that a good literary work doesn’t only talk about literature but also about other values. Poems written by Wunulde Syafinal and Taufik Effendi Aria contain some extrinstic elements which deal with religion, psychology, economy. Thus, these poems strengthen the existence of the poets who contribute meaningful values to the life of their readers.